Blind Eyes, Deaf Ears: Phenomenological Study on the Meaning of Local Figures of CSR of Semen Rembang - Yohana Ayu Astari; Nanang Krisdinanto; Yuli Nugraheni (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
This research focuses on the problems surrounding mining conflicts and the synergistic CSR (corporate social responsibility) program owned by PT Semen Gresik at the Rembang Factory in Timbrangan Village, Kab. Rembang, which includes areas directly adjacent to the location of the factory or source of raw materials (Ring 1). The purpose of this study is to describe the experiences and meanings of local leaders (informal leaders, who are divided into pro and contra groups) regarding the CSR program that carries the narrative of welfare. This study uses a qualitative approach and a phenemenological method, in which the researcher allows community leaders who are the research subjects to actively construct meaning through their intersubjective experiences related to the Synergy CSR program. Data collection was carried out through in-depth interviews to obtain the essence of the phenomenon that was observed and told from a first-person perspective. This study found that CSR Synergy is interpreted by local leaders (informal leaders) as a program that tends to formulate the needs of the target community with the perspective of their own interests, tends to be compiled and implemented based on an assessment of citizens' needs. Research subjects also interpret CSR as a program that make targeted societies increasingly dependent on, not empowering, and merely fulfilling statutory obligations as a formality or to create a public image since the company is responsible for exploiting the natural resources. The welfare narrative brought by the CSR program was interpreted by the research subjects as a strategy to trick the public to cover up the impact of environmental damage. In the end, this meaning has the implication of the emergence of apathy, which is reflected in the local imagery of a short-sighted ear (blind ear, deaf eye).